Evaluasi Pada Variasi Proses Bisnis Penanganan Pengaduan Dengan Menerapkan Process Mining Dan Quality Evaluation Framework (QEF) (Studi Kasus : Perusahaan Daerah Air Minum Kota Malang) - Dwi Asri Nuryulianti; Nanang Yudi Setiawan; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
PDAM Malang is one of company that provide water distribution service. One of the services provided is complaint service which will help customers's complaints. The most frequently reported complaints services within the last 6 months of September 2017 - February 2018 are non-flowing water, booth meter checks, increased usage, leaking pipes, leaking cob and road reconditioning. Mission of PDAM Malang is to improve and give service priority. However, based on reviews from website of PDAM Malang, most of people gave criticism related to the handling of complaints on PDAM. Based on observations, the business process flow of complaint-handling service has variations on certain conditions that may affect targets from those already established. Variations can be formed due to an uncertain condition in a business process, so that variation has a major influence on the ongoing activity. Therefore it is necessary to evaluate the variation of 6 business process complaint services. Getting the variation will be conducted through applying process mining that will get two variations, then the evaluation will be conducted by using Quality Evaluation Framework (QEF) method, so it will found 15 quality factor in 6 types of complaint. From the result of the evaluation, that was founded is one of quality factor that is not in accordance with the target and has no relation with the resulting variation, but there are some quality factors that can be achieved or in accordance with the target.